Financial literacy and motivation in University Mexican students. Gender gap and career choice - Arquero, José L.; Fernández-Polvillo , Carmen; Michel-Vázquez, Gracia Patricia; Jiménez-Cardoso , Sergio Manuel (Journal of Management and Business Education, 2025)
Educational choices, including active participation in innovations, are strongly connected with the perceptions of (I) self-competence, what the students think they can do successfully and (II) perceived goal fulfilment, or alignment between the activity objectives and students’ motivations. The main objectives of this paper are to compare the motivations, and the levels of financial literacy and related variables of students enrolled in two careers that potentially attract students with different characteristics and vocational interests and to test whether there exist a gender gap and if this gender gap prevails even when self-selection should have diminished it. A sample of 99 Mexican students enrolled in Law and Business degrees was obtained. Our results indicate that extrinsic motives are the main motivators of those students, revealing also differences by degree in most variables associated with numeracy. For financial literacy the gender gap prevails over self-selection and is similar in both degrees. Educational implications of the results are discussed.